Assessing the biogeographical and socio-ecological representativeness of the ILTER site network. (August 2021) - Wohner, Christoph; Ohnemus, Thomas; Zacharias, Steffen; Mollenhauer, Hannes; Ellis, Erle C.; Klug, Hermann; Shibata, Hideaki; Mirtl, Michael
Highlights: Biogeographical and socio-ecological representativeness of the ILTER network. "Representedness" values were calculated and used as indicators. Identification of gaps and biases of the network. Recommendations for the spatial extension of the site network. Abstract: The challenges posed by climate and land use change are increasingly complex, with rising and accelerating impacts on the global environmental system. Novel environmental and ecosystem research needs to properly interpret system changes and derive management recommendations across scales. This largely depends on advances in the establishment of an internationally harmonised, long-term operating and representative infrastructure for environmental observation. This paper presents an analysis evaluating 743 formally accredited sites of the International Long-Term Ecological Research (ILTER) network in 47 countries with regard to their spatial distribution and related biogeographical and socio-ecological representativeness. "Representedness" values were computed from six global datasets. The analysis revealed a dense coverage of Northern temperate regions and anthropogenic zones most notably in the US, Europe and East Asia. Significant gaps are present in economically less developed and anthropogenically less impacted hot and barren regions like Northern and Central Africa and inner-continental parts of South America. These findings provide the arguments for our recommendations regarding the geographic expansion for the further development of the ILTER network.